2003
DOI: 10.1063/1.1636534
|View full text |Cite
|
Sign up to set email alerts
|

Electron-beam-induced strain within InGaN quantum wells: False indium “cluster” detection in the transmission electron microscope

Abstract: InGaN quantum wells have been found to be extremely sensitive to exposure to the electron beam in the transmission electron microscope (TEM). High-resolution TEM images acquired immediately after first irradiating a region of quantum well indicates no gross fluctuations of indium content in the InGaN alloy. During only a brief period of irradiation, inhomogeneous strain is introduced in the material due to electron beam damage. This strain is very similar to that expected from genuine nanometer-scale indium co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
184
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 265 publications
(195 citation statements)
references
References 11 publications
11
184
0
Order By: Relevance
“…In the light of the Smeeton et al [16,17] papers, which suggested that the gross indium-rich clusters in InGaN quantum wells reported by many researchers might be due to electron beam damage, the Gerthsen group revised their earlier conclusions [11,12]. They observed that the indium concentration in the clusters increased with increasing irradiation time in the electron microscope.…”
Section: Does Tem Give Any Evidence For Genuine In Clustering?mentioning
confidence: 81%
See 3 more Smart Citations
“…In the light of the Smeeton et al [16,17] papers, which suggested that the gross indium-rich clusters in InGaN quantum wells reported by many researchers might be due to electron beam damage, the Gerthsen group revised their earlier conclusions [11,12]. They observed that the indium concentration in the clusters increased with increasing irradiation time in the electron microscope.…”
Section: Does Tem Give Any Evidence For Genuine In Clustering?mentioning
confidence: 81%
“…At low electron dose, the lattice fringe image of the quantum well and the lattice parameter map are both reasonably uniform ( figure 1a, 1c), [16,17]. We have studied the effect of 200, 300, and 400 keV incident electrons.…”
Section: Transmission Electron Microscopymentioning
confidence: 99%
See 2 more Smart Citations
“…4 The paper cites work by Smeeton et al, 5,6 which also relates the time evolution of dotlike structures of In x Ga 1−x N samples to heavy electron beam damage. These publications do not address the ion beam damage during sample preparation, which is equally relevant 7,8 and it is well known by now that high indium concentration regions with x Ͼ 0.7 are electron and ion beam induced artifacts.…”
mentioning
confidence: 99%